Brown adipose tissue activation as measured by infrared thermography by mild anticipatory psychological stress in lean healthy females - Robinson, Lindsay J.; Law, James; Symonds, Michael E.; Budge, Helen (Wiley, 2016)
Brown adipose tissue (BAT) has been implicated in the pathogenesis of obesity, type 2 diabetes and the metabolic syndrome and is a potential therapeutic target. Brown adipose tissue can have a significant impact on energy balance and glucose homeostasis through the action of uncoupling protein 1, dissipating chemical energy as heat following neuroendocrine stimulation. We hypothesized that psychological stress, which is known to promote cortisol secretion, would simultaneously activate BAT at thermoneutrality. Brown adipose tissue activity was measured using infrared thermography to determine changes in the temperature of the skin overlying supraclavicular BAT (TSCR). A mild psychological stress was induced in five healthy, lean, female, Caucasian volunteers using a short mental arithmetic (MA) test. The TSCR was compared with a repeated assessment, in which the MA test was replaced with a period of relaxation. Although MA did not elicit an acute stress response, anticipation of MA testing led to an increase in salivary cortisol, indicative of an anticipatory stress response, that was associated with a trend towards higher absolute and relative TSCR. A positive correlation between TSCR and cortisol was found during the anticipatory phase, a relationship that was enhanced by increased cortisol linked to MA. Our findings suggest that subtle changes in the level of psychological stress can stimulate BAT, findings that may account for the high variability and inconsistency in reported BAT prevalence and activity measured by other modalities. Consistent assessment of this uniquely metabolic tissue is fundamental to the discovery of potential therapeutic strategies against metabolic disease.